Characterization of new plasmids from methylotrophic bacteria - Brenner, V; Holubová, I; Benada, O; Hubácek, J (Antonie van Leeuwenhoek, 1991)
Several tens of methanol-utilizing bacterial strains isolated from soil were screened for the presence of plasmids. From the obligate methylotroph Methylomonas sp. strain R103a plasmid pIH36 (36 kb) was isolated and its restriction map was constructed. In pink-pigmented facultative methylotrophs (PPFM), belonging to the genus Methylobacterium four plasmids were detected: plasmids pIB200 (200 kb) and pIB14 (14 kb) in the strain R15d and plasmids pWU14 (14 kb) and pWU7 (7.8 kb) in the strain M17. Because of the small size and the presence of several unique REN sites (HindIII, EcoRI, NcoI), plasmid pWU7 was chosen for the construction of a vector for cloning in methylotrophs. Cointegrates pKWU7A and pKWU7B were formed between pWU7 and the E. coli plasmid pK19 Kmr, which were checked for conjugative transfer from E. coli into the methylotrophic host.
Keywords: methanol; Restriction Mapping; Escherichia coli; Conjugation, Genetic; Lactams; gramnegativní aerobní bakterie; Methanol; Drug Resistance, Microbial; Anti-Bacterial Agents; konjugace genetická; genetické vektory; plazmidy; Cloning, Molecular; klonování DNA; Plasmids; laktamy; antibakteriální látky; restrikční mapování; Genetic Vectors; Gram-Negative Aerobic Bacteria; antibiotická rezistence; Methylococcaceae